Factors Affecting Outcome Of Posterior Urethral Valve In Children Underwent Valve Ablation - Farhana, Rubaiyat; Sarwar, Md Khurshid Alam; Chowdhury, Tanvir Kabir (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Posterior Urethral Valve (PUV) is a congenital anomaly and the leading cause of chronic renal disease in boys. Several factors, such as age at presentation, high nadir serum creatinine, severe Vesicoureteric Reflux (VUR) recurrent UTIs, renal dysplasia, hypertension, albuminuria, growth failure, and primary therapy choice, are associated with poor longterm outcomes. However, studies on PUV in Bangladesh are limited. This study aimed to find out the factors affecting outcome of Posterior Urethral Valves (PUV) in children. Materials and methods: This prospective observational study was conducted at the Department of Pediatric Surgery, Chittagong Medical College Hospital (CMCH) Chattogram, Bangladesh, from April 2023 to September 2024. A total of 27 Children aged between 1 day to 12 years having posterior urethral valve were included. Age, type of valve, type of surgery, operating time, symptoms, presence of VUR, UTIs, Serum creatinine, anterior and posterior urethral ratio in micturating cystourethrogram were recorded and risk factors for adverse outcome and mortality were analysed. Results: The mean age of participants was 33.65±36.30 months, with 63% being children, 29.6% infants and 7.4% newborns. Type I posterior urethral valves were found in 88.9%, while 11.1% had Type III. Surgery types included valve fulguration (55.6%) and resection (44.4%) with a median operation duration of 22 minutes. Post-operative improvements were significant: dribbling of urine reduced from 85.2% to 20.8% (p < 0.001) recurrent UTIs from 59.3% to 12.5% (p = 0.001), and VUR from 51.9% to 11.1% (p = 0.008). Serum creatinine decreased from 0.9 mg/dL to 0.5 mg/dL (p < 0.001), and the posterior-to- anterior urethral ratio improved from 2.50 to 2.0 (p < 0.001). Overall, 88.9% of patients showed improvement, though 11.1% (n=3) died, with no significant factors associated with mortality. There were no significant differences in outcomes between the two surgical approaches (p>0.05). Conclusion: Surgical intervention in posterior urethral valves resulted in significant improvements in urinary symptoms and renal function, with no single factor linked to poor outcomes, highlighting the need for comprehensive management. JCMCTA 2025 ; 36 (2) : 13-18